Understanding and mitigating vulnerable bycatch in southern African longline and trawl fisheries - Petersen, Samantha Lara (Department of Environmental and Geographical Science, 2016)
Over the past decade there has been global concern about the bycatch of seabirds, turtles and sharks in fishing operations, in particular longline and trawl fisheries, which have been widely held responsible for their declining population s and threatened conservation status. This thesis addresses the issue of bycatch in a holistic manner, taking into account that species, whether they be target or non-target, do not exist in isolation from each other and their environment. South African fisheries incidentally catch approximately 21 000 seabirds, 165 turtles and 43 000 pelagic sharks per year, including 21 Endangered species. Decreasing CPUE and size-frequency data for Blue Prionace glauca and Short- finned Mako Sharks Isurus oxyrinchus caught in the large pelagic longline fishery suggests exploitation of these species is unsustainable. A decreasing trend in the biomass index was also observed for the Yellow-spotted Catshark Scyliorhinus capensis and the Biscuit Skate Raja. straeleni. An argument for the likelihood of fisheries mortality contributing to the slower than expected turtle population recovery rates is presented, which is supported by results from satellite tracking of Leatherback Turtles Dermochelys coriacea indicating a high degree of overlap with fishing effort. Satellite tracking of Black-browed Thalassarche melanophrys and White-capped T. steadi Albatrosses reveal striking differences in their foraging patterns and presents evidence that Black-browed Albatrosses, in particular, forage to a large extent on natural prey, despite the availability of discards from fishing vessels in the Benguela. Therefore, given the high albatross mortality in the trawl fishery, the benefit of a management decision to limit discarding as a mitigation measure is likely to outweigh the disadvantage of reduced food supply. Reducing bycatch is dependent on the development of effective and relatively inexpensive methods which do not impact on target catches and/or other vulnerable species. In the demersal longline fishery, two methods of optimising line sink rates to reduce seabird bycatch were investigated: increasing mass of weights and decreasing the spacing between weights. This study indicated that while the target species is unlikely to be affected by increased weighting, other vulnerable species of fish and sharks may be affected. Other mitigation experiments investigated line sinking rates and the use of circle hooks in pelagic longline fisheries. The implications of night setting on Swordfish Xiphias gladius catches, fishery closure during full moon and the appropriateness of the international standard 5% fin to trunk ratio for the South African fishery, were also investigated. Lastly, the spatial and temporal overlap of catches of seabirds, turtles and sharks were investigated through a conservation planning exercise using MARXAN and potential areas for closure identified.